Local Planning in Nepal: Understanding Among Local Officials - Adhikari, Govinda (Historical Journal, 2024)
This study describes local government officials’ understanding of planning provisions, particularly annual planning, in Nepal to identify gaps and improve effectiveness. Based on document reviews, interviews, and focus group discussions with officials from five local governments each in Lumbini and Madhesh Provinces and two in Koshi, it reveals significant knowledge gaps, particularly among grassroots officials. The study highlights the need for enhanced training and capacity-building to address these deficiencies, improve decision-making, and support sustainable development. Recommendations include strengthening training programs for both officials and community leaders who can exert pressure on local officials to implement provisions improving information dissemination, and reinforcing accountability mechanisms.